Pengaruh Model Pembelajaran Ekspositori Berbantuan Scaffolding Dan Advance Organizer Terhadap Hasil Belajar Fisika Peserta Didik Kelas X - Ahmad Saifi Hasbiyalloh; Ahmad Harjono; Ni Nyoman Sri Putu Verawati (Department of Physics Education, Universitas Mataram, 2017)
This research aimed to examine the effect of expository learning model scaffolding assisted and advance organizer toward physics learning outcome the students of class X. This is a quasi experiment with pretest-postest control group design. The population of this research is all students of class X IPA SMAN 4 Mataram. The sampling technique used is purposive sampling. There are two samples taken that is sample as a class given treatment in the form of learning using scaffolding expository aided learning model (class X IPA 1) and classes treated using expository learning model assisted advance organizer (class X IPA 2). The data of learning outcome is obtained by using the multiple-choice test of 25 questions. After hypothesis testing using statistical test (t-test separated varian). The first hypothesis testing showed that tcount > ttable which means that Ho1 is rejected and Ha1 is accepted. The second hypothesis testing showed that, tcount > ttable which means that Ho2 is rejected and Ha2 is accepted. Based on the hypothesis test, it can be concluded that there is effect of expository learning model with scaffolding and advance organizer to the physics learning outcome of students.